Diagnosis of autoimmune gastritis in patients with different status of Нelicobacter pylori infection: a medical decision support system - A. V. Gubanova; M. A. Livzan; S. I. Mozgovoi; D. V. Turchaninov (Лечащий Врач)
Background. Autoimmune inflammation in the gastric mucosa and Helicobacter pylori (H. pylori) infection are the main etiologic factors of chronic gastritis. Diagnostics of H. pylori bacteria is regulated by clinical guidelines for the management of patients with gastritis and duodenitis, while verification of autoimmune inflammation in the gastric mucosa is often delayed. An additional difficulty in the diagnosis of аutoimmune inflammation in the gastric mucosa is the combination with H. pylori, due to the shift of the clinician attention only to this etiologic factor without searching for other possible causes of chronic gastritis. Taking this into account, the development of a system for supporting medical decision support system to improve the verification of autoimmune inflammation in the gastric mucosa in individuals with different status of H. pylori infection is of particular relevance.Objective. To identify diagnostic significant clinical, endoscopic and morphological signs of autoimmune inflammation in the gastric mucosa in patients with different statuses of H. pylori infection, followed by the development of a medical decision support system.Materials and methods. An open, cohort, cross-sectional study was performed with the 124 subjects with chronic gastritis. Considering the presence of autoimmune inflammation in the gastric mucosa and the status of infection H. pylori, all patients were divided into three groups: the main group consisted of 35 patients with autoimmune inflammation in the gastric mucosa, comparison group 1 – 38 patients with аutoimmune inflammation in the gastric mucosa + H. pylori-associated, comparison group 2 – 51 patients with H. pylori-associated gastritis. To assess the diagnostic significance of the signs for the purpose of diagnosis Autoimmune inflammation in the gastric mucosa was used Bayes' theorem. All study participants were assessed for the presence of gastrointestinal symptoms using the GSRS questionnaire, as well as an analysis of the incidence of manifestations of anemic, sideropenic syndromes, vitamin B12 deficiency, both at the onset of the disease and at the time of inclusion in the study, with an assessment of their diagnostic significance for аutoimmune inflammation in the gastric mucosa. The calculation of the informativeness of the data on the comorbidity of autoimmune inflammation in the gastric mucosa with other autoimmune diseases was performed, including an analysis of previously received therapy for concomitant pathology. The calculation of the diagnostic significance of results of laboratory studies, endoscopic and morphological examination of biopsies of the gastric mucosa was performed.Results. Diagnostic significant signs of the presence of autoimmune inflammation in the gastric mucosa in patients with different status of H. pylori infection were determined: female gender, manifestations of dyspepsia syndrome (belching of air, as well as acidic or bitter contents, nausea, a feeling of distension, fullness in the epigastric), symptoms of vitamin B12 deficiency, anemic and sideropenic syndromes, the presence of autoimmune thyroiditis, vitiligo, type 1 diabetes mellitus, decreased hemoglobin and mean corpuscular hemoglobin concentration values, decreased iron and vitamin B12, the presence of endoscopic and histological signs of atrophy and intestinal metaplasia of the body of the stomach.Conclusion. Based on the results of the study, a medical decision support system was developed to detect аutoimmune inflammation in the gastric mucosa in patients with different status of H. pylori infection. A model for assessing the risk of the presence of аutoimmune inflammation in the gastric mucosa has been created in two versions, differing in the volume of the signs used, which can help a practicing physician in identifying patients at risk already during the initial visit.